Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan Tentang Anemia Pada Remaja Putri di SMA Kesatrian 2 Semarang - Efri Susanti Mesi; Mudy Oktiningrum; Nella Vallen (Pusat riset dan Inovasi Nasional, 2024)
Background: Anaemia is a condition with lower-than-normal haemoglobin levels and red blood cells. Iron nutritional anaemia in young women is at higher risk because it causes a person to experience decreased body resistance, making them susceptible to health problems (Anggoro, 2020). Normal Hb levels in female adolescents >12 g/dL, women of childbearing age 12–14 g/dL, pregnant women 11 g/dL, and males >13 g/dL. The prevalence of anaemia among young women in Semarang City is 43.75% (Semarang City Health Office, 2019). Based on preliminary studies at SMA Kesatrian 2 Semarang from class X, XI, and XII representatives, such as BP checks, conjunctival and skin examinations. After a simple examination, it was found that there were 3 class X who experienced symptoms of anaemia. Eight students in class XI experienced symptoms of anemia. In class XII, four people experienced symptoms of anaemia. Purpose: This study aimed to determine the effect of health education on the level of knowledge of anaemia in young female at SMA Kesatrian 2 Semarang.Method: This study used the pre-experimental design method with a one-group pre-test and post-test design approach. The sampling technique used was total sampling with a sample size of 55 respondents, and the research location was at SMA Kesatrian 2 Semarang. The data analysis used was the Wilcoxon test with the Shapiro-Wilk data normality test. Results: Based on data analysis, we obtained good knowledge from 51 (92.7%) respondents. The results of the Wilcoxon statistical test, namely a p-value of 0.000 (<0.005) and a potential health education value of 6.473x, affect the level of knowledge about anaemia in female adolescents. It can be concluded that Ha is accepted, and Ho is rejected; that is, there is an effect of providing health education on the level of knowledge about anaemia in young female at SMA Kesatrian 2 Semarang. Conclusion: Adolescents need to be given additional health education about anaemia to better recognize the signs and symptoms and how to avoid it.